Analisis Tindak Tutur Direktif dalam Ceramah dr. Aisyah Dahlan - Kahar, Kurnia Putri; Yusmah, Yusmah; Hanafi, Muhammad; Mahmud, Nurlaelah (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to analyze directive speech acts in Dr. Aisyah Dahlan's lectures, especially in lectures entitled Building a Harmonious and Romantic Family with a focus on the forms, functions, and communication strategies used. Data collection was conducted in January 2025 with a descriptive qualitative approach. Data were obtained from lecture videos uploaded on Dr. Aisyah Dahlan's official YouTube channel, through listening, transcription, and recording techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the most dominant form of directive speech acts was interrogative, followed by declarative and imperative. The most frequently used function was questions, followed by advice, requests, orders, prohibitions, and granting permission. The communication strategy used includes five elements in the Lasswell model, namely Dr. Aisyah Dahlan as a communicator (who?). Each message has a different purpose, such as building interaction, creating closeness, arousing emotions, and making it easier for the audience to understand the material (what?). The lecture was delivered live and broadcast on YouTube (which channel?) to the general audience (to whom?). This strategy produced a communication effect in the form of increased attention, the emergence of emotional responses, and the growth of audience awareness of the contents of the lecture message (with what effect?).